Advertising theories in impulse purchase elements for iTV advertisement - Che Omar, Azizah; Sarif, Siti Mahfuzah; Shiratuddin, Norshuhada (2015)
This paper reports an ongoing study related to the design of conceptual design model of interactive television (iTV) advertisement towards impulse purchase tendency.Despite many studies have been proposing factors of impulse purchase in many different advertising medium like website, mobile, traditional retail store, and traditional television; none of the impulse purchase model is dedicated towards impulse purchase tendency for iTV advertising. Therefore, one of the objectives of this study is to identify impulse purchase elements that are suitable for iTV advertising. In particular, this paper describes the connection between the identified impulse purchase elements of iTV advertisement with the advertising theories through content and comparative analysis.The finding shows that the elements of impulse purchase for iTV advertising can be classified into nine; information, influence, emotion, attention, message,acceptance, still media, motion media, and interactivity. In which all of the aforementioned elements are substantiated by advertising theories as further discussed in this paper.